2001
DOI: 10.1021/bp000139d
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Removal of Protein Aggregates by Annular Chromatography

Abstract: The removal of polymeric proteins from their monomers is a frequently encountered separation task, especially in the polishing step of therapeutic proteins. Continuous separation of protein polymers from monomers by annular chromatography using size exclusion chromatography has been studied regarding the resolution, recovery, fouling, and productivity and has been compared to conventional chromatography. An IgG preparation rich in aggregates was used as a model protein mixture. Under conditions that maximized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…A higher flow rate of regeneration buffer resulted in damage of the upper gel layer and additional dispersion effects at the outlet of the nozzle in the surrounding glass beads. Similar effects have been observed by Iberer et al [20] and Buchacher et al [21].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A higher flow rate of regeneration buffer resulted in damage of the upper gel layer and additional dispersion effects at the outlet of the nozzle in the surrounding glass beads. Similar effects have been observed by Iberer et al [20] and Buchacher et al [21].…”
Section: Resultssupporting
confidence: 88%
“…Dispersion effects caused by the density and viscosity differences between the feed stream, regeneration buffer and eluent buffer resulted in an increase of outlet fractions containing the regenerate. Broadening of the regenerate peak during extended operation might lead to reduction of resolution of the various protein containing fractions and therefore limitation of such a continuous process [21].…”
Section: Discussionmentioning
confidence: 99%
“…The standard method for the determination of aggregate content combines high-performance size-exclusion chromatography (SEC) with UV detection (Buchacher et al, 2001). However, traces of large protein aggregates cannot be detected by UV absorbance due to its limited sensitivity since these aggregates usually exist in low abundance, often smaller than 0.3% of the total hIgG content (Ahrer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The recovery ratio or yield is influenced by operating conditions, the stability of the protein, the source of the protein, and the presence of degrading enzymes. Buchacher et al [26] showed that this equation is also valid for annular chromatography. The recovery ratio is defined as throughput of protein at a certain purity where m p is the amount of pure protein:…”
Section: Productivitymentioning
confidence: 97%
“…The nonlinear multicomponent Langmuir isotherm correctly predicts the decrease in resolution as the concentration is increased. Buchacher et al [26] observed progressive fouling at high feed concentrations (50 mg IgG/ml) and, consequently, the separation resolution deterioriated.…”
Section: Effect Of Feed Concentrationmentioning
confidence: 99%